History of Tribology in Ancient Northeast Asia - The Japanese Sledge and the Chinese Chariot - - Yorikazu Shimotsuma (Japanese Society of Tribologists, 2011)
There are a lot of tribological technologies in the sledge and the carriage. The origin of the sledge and the carriage can be seen in the Sumerian pictographic script excavated from the temple of Inanna in Uruk (modern Warka, Iraq). Sledges gradually evolved over time, from sledges that moved on rollers, to more advanced carriages with wheel such as war chariots, two-wheeled carts and four-wheeled wagons. In this paper, the Japanese sledges and Chinese chariots in ancient Northeast Asia are discussed from a viewpoint of the history of tribology. In ancient Japan, heavy items such as giant trees or stones were transported by the Shura which is a Y-shaped or a V-shaped wooden sledge. The coefficient of rolling friction was obtained by a transport experiment using a manufactured Shura. In ancient China, various types of ancient Chinese chariots with one axle and two wheels were excavated at several archaeological sites. The world's first cast iron products were made in ancient China around 500 B.C. The ancient Chinese chariots had been developed by using cast iron axle bearings. It can be seen from these results that excellent tribological technology existed in ancient Japanese sledges and ancient Chinese chariots.